Clinical Application of Ultrasound Guidance for Parametrial Treatment of Advanced Cervical Cancer. (11th December 2019) - Lin, Yuanqiang; Cheng, Guanghui; Shi, Dan; Li, Hequn; Teng, Dengke; Zhao, Zhipeng; Mao, Zhuang; Wang, Hui
Abstract : Objectives: To evaluate the accuracy of ultrasound (US) in determining the positions of parametrial implants by comparing US with magnetic resonance imaging (MRI) for advanced cervical cancer. Methods: Patients undergoing brachytherapy with parametrial implantation for cervical cancer from February 2017 to February 2019 were involved in the study. The transverse section of the cervix (surface S1 ) and the transverse section 1 cm above the external cervix (surface S2 ) were selected from MRI and US images as the observation planes. In the MRI observation plane, the distances between the uterine titanium needles and the uterine tube/implanter were set as M1 to M4 ; in the US observation plane, the distances between the uterine titanium needles and the uterine tube/implanter were set as D1 to D4 . The differences and consistency in M and D of each group were then compared. Results: There were no significant differences between M and D in each group ( P = .058; P = .821; P = .870; and P = .936, respectively). The intraclass correlation coefficients of M and D in each group were 0.970, 0.968, 0.952, and 0.956. A regression analysis showed that the relationships between M and D in each group were as follows: M1 = 0.9449D1  + 0.1812; M2 = 0.9463D2  + 0.0965; M3 = 0.9176D3  + 0.1233; and M4 = 0.9253D4  + 0.1224. Conclusions: In parametrial brachytherapy for cervical cancer, US can accurately determine the positions of parametrial implantation needles, which is already applicable on MRI, and can provide assistance in parametrial brachytherapy for advanced cervical cancer.